4 Pilar Gizi Seimbang Dengan Status Gizi Dalam Penggunaan Bahan Makanan Sederhana - Ramli, Rachmat; Mainassy, Meilisa Carlen; Leli, Leli; Saad, Rahmiyani; Jariyah, Ainun; Putra, Egy Sunanda; Hasibuan, Evis Ritawani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Nutritional status is the state of the body as a result of food consumption and the use of nutrients. Adolescents must get a balanced intake of nutrients according to their needs in order to achieve optimal growth and development. Imbalances in intake and development lead to nutritional problems. One of the causes of nutritional problems is lack of knowledge. This PkM aims to determine the relationship between knowledge about balanced nutrition and the nutritional status of adolescent girls. Based on a preliminary survey at SDN Makassar, the composition of foodstuffs consumed by students every day does not meet the guidelines for balanced nutrition. This community service prioritizes counseling on foods that are in accordance with balanced nutrition and the selection of healthy snacks for students of SDN Makassar. Counseling is carried out with various media, namely audio-visual media, posters and booklets. Through this PKM, it is expected that there will be a change in behavior patterns in school children to consume foods that are in accordance with balanced nutritional guidelines.